EVALUASI PENERAPAN PEMBELAJARAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA BELAJAR DI UPT SPF SD NEGERI GARUDA KOTA MAKASSAR - Munawir; Mansyur; Baso Intang Sappaile (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is an evaluative research which aims to evaluate the implementation of differentiated learning in the Independent Learning Curriculum at UPT SPF SD Negeri Garuda Makassar. The research method used is the mixed methods Stake model (Antecedents, Process, Outcomes). Data collection in this research was carried out through questionnaires and interviews addressed to school principals, teachers and students in class IV A, IV B, V A, V B and Class VI. The data analysis used is quantitative and qualitative descriptive analysis. The success criteria for this research are based on evaluating aspects in the Stake evaluation component, namely Antecedents, Process, Outcomes. The research results show that 1) The implementation of Differentiated Learning in the Independent Learning Curriculum based on the Context (Antecedents) component in classes 4 A, 4 B, 5 A, 5 B and Class 6 has gone very well; 2) The implementation of Differentiated Learning in the Independent Learning Curriculum based on the Process (Transactions) component in classes 4 A, 4 B, 5 A, 5 B and Class 6 has gone very well; 3) Differentiated Learning in the Independent Learning Curriculum based on the Output component (Outcomes) in classes 4 A, 4 B, 5 A, 5 B and Class 6 has been going well